2020
DOI: 10.1111/nmo.14020
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the food additive monosodium glutamate on cisplatin‐induced gastrointestinal dysmotility and peripheral neuropathy in the rat

Abstract: Background: Cisplatin is an antineoplastic drug known to produce intense vomiting, gastric dysmotility, and peripheral neuropathy. Monosodium glutamate (MSG) is a flavor enhancer with prokinetic properties potentially useful for cancer patients under chemotherapy. Our aim was to test whether MSG may improve gastrointestinal motor dysfunction and other adverse effects induced by repeated cisplatin in rats. Methods: Male Wistar rats were exposed or not to MSG (4 g L −1) in drinking water from week 0 to 1 week af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
31
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(38 citation statements)
references
References 70 publications
6
31
1
Order By: Relevance
“…4 MSG, alone or combined with vincristine, did not modify body weight or food and liquid intake, in agreement with previous results in control rats 21 or rats treated with another antineoplastic drug, cisplatin. 19 Chronic vincristine administration induced mechanical allodynia (a sign of peripheral neuropathy) when the Von Frey test was applied 1 week after treatment finalization, also in agreement with previous reports. 4,30,31 In this study, MSG could not prevent the development of neuropathic pain caused by vincristine.…”
Section: General Health Parameterssupporting
confidence: 91%
See 1 more Smart Citation
“…4 MSG, alone or combined with vincristine, did not modify body weight or food and liquid intake, in agreement with previous results in control rats 21 or rats treated with another antineoplastic drug, cisplatin. 19 Chronic vincristine administration induced mechanical allodynia (a sign of peripheral neuropathy) when the Von Frey test was applied 1 week after treatment finalization, also in agreement with previous reports. 4,30,31 In this study, MSG could not prevent the development of neuropathic pain caused by vincristine.…”
Section: General Health Parameterssupporting
confidence: 91%
“…Mechanical sensitivity was assessed in cohort 2 by measuring the withdrawal threshold to calibrate Von Frey hairs (2-60 g; Bioseb Instruments, USA) after treatment finalization, on week 3 (as previously described 4,19 ). Rats were placed individually on an elevated iron mesh in a clear plastic cage and allowed to adapt to the testing environment for at least 10 min 2-3 days before the assessment.…”
Section: Assessment Of Mechanical Sensitivitymentioning
confidence: 99%
“…As expected, in this study the transit pattern in M-N group was similar to that previously found by other authors and also by our group. 12,1719…”
Section: Discussionmentioning
confidence: 99%
“…As expected, in this study the transit pattern in M-N group was similar to that previously found by other authors and also by our group. 12,[17][18][19] The present study benefits from the performing of a comprehensive analysis of the faecal pellets collected during the radiographic session. The percentage of stained faecal pellets showed a progressive increase from T4 to T24.…”
Section: X-ray Study Of Gastrointestinal Transit In Male Rats Under N...mentioning
confidence: 99%
“…Cisplatin is a broad-spectrum and highly effective platinum-based antitumor drug, which is widely used in the treatment of various solid tumors such as lung cancer ( Wang et al, 2021 ), gastric cancer, breast cancer ( Vidra et al, 2022 ), ovarian cancer ( Muhanmode et al, 2021 ), and bladder cancer. However, the dose-limiting toxicities of cisplatin, such as nephrotoxicity ( Ma et al, 2021 ), ototoxicity ( Tserga et al, 2020 ), neurotoxicity, hepatotoxicity ( Abd Rashid et al, 2021 ), cardiotoxicity ( Xu et al, 2021 ), and gastrointestinal toxicity ( Lopez-Tofino et al, 2021 ), severely limit its application in clinical oncology. Among them, gastrointestinal toxicity is the most essential clinical dose-limiting side effect, which dramatically affects the antitumor efficacy of cisplatin, seriously affects the quality of life of patients, and even needs to stop chemotherapy ( Blijlevens et al, 2000 ).…”
Section: Introductionmentioning
confidence: 99%